Development of Soft Drink with Addition of Baccharis dracunculifolia Extract: Physicochemical and Antioxidant Analyzes (Research, Society and Development, 2022)
Consumption of soft drinks has increased in recent decades, and is associated with increased prevalence of obesity, weight gain and diabetes. Studies show a direct relationship between diet and health which, added to the growing interest of some individuals in consuming healthier foods, has increased the interest of the food industry in developing new products. Rosemary (Baccharis dracunculifolia) is known to have a diversity of phenolic compounds. Among the effects of the use of B. dracunculifolia already observed in the literature, we can mention a drop in fasting capillary blood glucose levels and protection from damage to organs such as the liver, kidneys and pancreas. When added to foods, their antioxidant compounds are able to delay the formation of oxidative products, maintain the nutritional quality of the food and increase its shelf life. The present work carried out chemical and antioxidant analysis of an orange soft drink with the addition of B. dracunculifolia extract. Under the conditions of this work, high levels of total phenolic compounds (515.1µg Eq GAE/g) and high free radical scavenging capacity ABTS (12356.6 µM trolox/g) and DPPH (0.851 µM trolox/g) were obtained in addition to a high iron III reducing antioxidant power (18354 µM ferrous sulfate/g). The orange soft drink enriched with extract of B. dracunculifolia developed in this work showed antioxidant power even in its lowest concentrations.